THE ROLE OF THE NATIVE LANGUAGE IN THE FORMATION OF MORAL QUALITIES OF A SCHOOLCHILD (Eureka Journal of Computing Science & Digital Innovation, 2025)
The article examines the role of the native language as a key factor in the formation of moral qualities of a schoolchild. The influence of language on the formation of moral norms, the development of spiritual values, the formation of a culture of behavior and speech is analyzed. Special attention is paid to the educational potential of the language in the educational process. It is shown that the native language is the basis of personal development, moral consciousness, emotional sensitivity and social maturity of the student.
Keywords: Native language, moral qualities, schoolchild, spiritual education, culture of speech, values, personal development, speech behavior.